Determining the level of comprehension of registered dietitians in South Africa with regard to the glycemic index (GI) used in the treatment of Diabetes Mellitus - Strydom, Hildegard (Stellenbosch : University Stellenbosch, 2010)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2009.